2013 IEEE International Symposium on Performance Analysis of Systems and Software (ISPASS) 2013
DOI: 10.1109/ispass.2013.6557170
|View full text |Cite
|
Sign up to set email alerts
|

Power measurement techniques on standard compute nodes: A quantitative comparison

Abstract: Energy efficiency is of steadily growing importance in virtually all areas from mobile to high performance computing. Therefore, lots of research projects focus on this topic and strongly rely on power measurements from their test platforms. The need for finer grained measurement data-both in terms of temporal and spatial resolution (component breakdown)-often collides with very rudimentary measurement setups that rely e.g., on non-professional power meters, IMPI based platform data or model-based interfaces s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 18 publications
(19 reference statements)
2
69
0
4
Order By: Relevance
“…This simple approach has been validated with hardware power meters by third parties studies for recent NVIDIA GPUs and Intel CPUs [15], showing that it produces accurate results [16,31]. In this approach we cannot monitor the power drain of the motherboard and other ancillary hardware; recent studies have shown however that the power drain of those components is approximately constant in time and weakly correlated with code execution [15,32]. In-band measurements may also introduce overheads, which in turn may affect our results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This simple approach has been validated with hardware power meters by third parties studies for recent NVIDIA GPUs and Intel CPUs [15], showing that it produces accurate results [16,31]. In this approach we cannot monitor the power drain of the motherboard and other ancillary hardware; recent studies have shown however that the power drain of those components is approximately constant in time and weakly correlated with code execution [15,32]. In-band measurements may also introduce overheads, which in turn may affect our results.…”
Section: Methodsmentioning
confidence: 99%
“…732MHz) ≈ 7% of the total consumed energy of the computing node can be saved, with respect to the default behavior, without impacting performances. 15 …”
Section: Full Code On Multi-gpusmentioning
confidence: 99%
“…One factor which hides the problems with Et n metrics is the small range of power consumption exhibited by modern hardware running HPC workloads as a result of high base power consumption and marginal differences under load [10]. Fig.…”
Section: Justification Of Et Nmentioning
confidence: 99%
“…The PowerMon2 [14] project describes small boards that can be used to instrument a large x86 cluster. Hackenberg et al [15] describe various power measurement techniques (including Intel running average power limit (RAPL) power estimates), but again, primarily looking at x86 devices.…”
Section: Cluster Power Measurementmentioning
confidence: 99%